PERANCANGAN APLIKASI MANAJEMEN KEUANGAN DIGITAL BERBASIS MOBILE DENGAN FITUR VISUALISASI DATA DAN LAPORAN OTOMATIS - Alyssa Cheniaka Febriawan (Jurnal Teknologi Informatika dan Rekayasa Terapan, 2026)
This study is motivated by the rapid growth of digital transformation that significantly impacts financial management, especially in small businesses and organizations. However, many users still rely on manual recording or applications that are not integrated with real-time data visualization features, resulting in delayed decision-making and limited data utilization. The purpose of this research is to design and develop a mobile-based digital financial management application equipped with data visualization and automatic financial reporting features. The research method used is Research and Development (R&D) with an Agile development model, which includes requirement analysis, system design using UML, application implementation, and system testing using Black Box Testing. Data were collected through literature studies and observations of existing financial management issues. The results show that the developed application is able to simplify transaction recording, present financial data in informative visual formats, and generate automatic financial reports. In addition, the system functions properly based on functional testing results. In conclusion, the mobile-based digital financial management application can improve efficiency, accuracy, and usability in financial management.